Differences between Spatial and Visual Mental Representations - Sima, Jan Frederik; Schultheis, Holger; Barkowsky, Thomas (Frontiers in Psychology, 2013)
This article investigates the relationship between visual mental representations and spatial mental representations in human visuo-spatial processing. By comparing two common theories of visuo-spatial processing - mental model theory and the theory of mental imagery - we identified two open questions: 1) which representations are modality-specific, and 2) what is the role of the two representations in reasoning. Two experiments examining eye movements and preferences for under-specified problems were conducted to investigate these questions. We found that significant spontaneous eye movements along the processed spatial relations occurred only when a visual mental representation is employed, but not with a spatial mental representation. Furthermore, the preferences for the answers of the under-specified problems differed between the two mental representations. The results challenge assumptions made by mental model theory and the theory of mental imagery.